Appendiceal carcinoma presenting as a rapidly enlarging abdominal mass. (July 2021) - Gilani, Mohammad; Iskaros, Mina; Nahidi, Seyed Mohammad; Mehta, Nisarg; Ahmed, Leaque
Abstract: Introduction: Appendiceal adenocarcinomas, although rare, usually present as slow-growing masses. Rarely, do they rapidly enlarge into large abdominal masses over a short period of time. Generally, we attribute rapidly growing abdominal masses to sarcomas, desmoid tumors, or gynecological masses. We present a case of a rapidly growing appendiceal adenocarcinoma in an elderly patient. Case presentation: We report a case of an 83-year-old-male who presented with a one-month history of abdominal pain. A computer tomography (CT) scan identified a lower pelvic mass measuring 7.39 cm × 5.40 cm. A biopsy was done which revealed appendiceal carcinoma. A plan for radiotherapy to reduce the tumor size was made and the patient was discharged. However, the patient returned after three weeks due to worsening abdominal pain and a CT scan identified a significant enhancement in the tumor size. The patient underwent debulking surgery. Pathology of the specimen identified adenocarcinoma of the appendix. Discussion: A rapidly growing carcinoma of the appendix is rare as they are known to have a slow growth rate. A swift diagnosis and intervention are required as these rapidly enhancing neoplasms in the abdomen can become unresectable and metastasize. Although there are various methods of treatment for appendiceal carcinomas, the rapid growth rate and lack of response to radiation required debulking surgery. Conclusion: There exist a myriad of differential diagnoses for a rapidly growing mass in the abdomen. We are presenting the first documented case of a rapidly growing appendiceal adenocarcinoma. Surgeons should be aware of the variety of differentials in such cases. Highlights: Appendiceal carcinomas with such a rapid enhancement in size are quite rare. Having an appendiceal carcinoma for a rapid gastrointestinal tumor can facilitate immediate management in such cases. The array of differentials in such cases could lead to delays in management and treatment.